Uso de prótese expansora auxiliando na reabilitação com prótese ocular - Iyda, Bruno Garib [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Treatment with ocular prosthesis plays an important role in preservation of facial esthetics, and properly stimulate the tissue growth. However, the ideal is that the prosthesis is adapted as soon as the problem is installed, minimizing sequelae and disturbances during the orbital growth. The purpose of this case report is to describe the rehabilitation of the eyeball of a two months old pacient, emphasizing indications and limitations. Clinical case: Patient, 2 months old, female was referred to College of Dentistry of Araçatuba (FOA / UNESP) for an eyeball rehabilitation. During the physical and clinical examinations, the pacient was diagnosed with an absence of the eyeball due to domestic trauma, which caused eyelid collapse and facial deformity. The treatment plan proposed was the manufacture of an expander prosthesis and posteriorly, the rehabilitation with ocular prosthesis. The expander prosthesis was made of acrylic resin and remained in the patient's anophthalmic socket for 60 days in order to return the volume needed. After this period an ocular prosthesis was made of N1 and colorless acrylic resin; artificial iris was obtained by painting a cardboard disk with oil paint. After the treatment, it can be seen that Expander prosthesis provided the increase of the anophthalmic cavity and promoted the patient's adaptation in relation to the occurred situation. The Ocular prosthesis set the aesthetic balance of the face which will eventually reflect positively on psychological and social development of the child

O tratamento com próteses oculares desempenha papel importante na preservação da estética facial, além de estimular adequadamente o crescimento dos tecidos. No entanto, o ideal é que a prótese seja adaptada tão logo o problema se instale, minimizando sequelas e distúrbios durante o crescimento orbital. O relato de caso teve por finalidade descrever a reabilitação do globo ocular de uma paciente com 2 meses de idade, ressaltando indicações e limitações. Caso clínico: Paciente, com 2 meses de idade, do sexo feminino foi encaminhada à Faculdade de Odontologia de Araçatuba (FOA/UNESP), para reabilitação do globo ocular. Durante os exames físico e clínico pode-se verificar ausência do globo ocular, devido a trauma doméstico, o que ocasionou colapso palpebral e deformidade facial. Como plano de tratamento foi proposto a confecção de prótese expansora para que posteriormente realizasse a reabilitação com prótese ocular. A prótese expansora foi confeccionada em resina acrílica e permaneceu na cavidade anoftálmica da paciente por 60 dias, a fim de devolver o volume necessário. Após este período a prótese ocular foi confeccionada em resina acrílica N1 e incolor; a íris artificial foi obtida por meio da pintura de disco de cartolina com tinta à óleo. Ao fim do tratamento, pode-se observar que a prótese expansora proporcionou aumento da cavidade anoftálmica além de promover adaptação da paciente em relação à situação ocorrida. A prótese ocular estabeleceu o equilíbrio estético da face, o que futuramente irá refletir de modo positivo no desenvolvimento psíquico social da paciente
Keywords: Olho artificial; Órbita; Crescimento e desenvolvimento; Eye, Artificial